Review on Teaching Ethical Hacking (International Journal of Innovative Research in Computer Science & Technology, 2022)
The word hacker generally characterize  the practice or performance of investigating & carry out  trial with computer networks as computer communications  grew more ubiquitous with the emergence of the Internet.  However, when devices with tools and connected network  became more commercialized, the system also became  assets with ostensible limitations, & violating such borders  became illegal. The number of programs teaching ethical  hacking is rapidly increasing. The requirement for a  comprehensive understanding of tactics and assailants is at  the heart of the case for training in ethical hacking field.  Many peoples argue, however, that getting training in offensive hacking skills advances communal menace by  promising followers to take part in illegitimate behaviour.  Ethics instruction pervades associated curricula, according  to proponents of teaching ethical hacking, giving students  enough preparation to recognize the hazards and adopt  healthy actions. This article looks at ways to reduce the  danger of students using abilities learned in an ethical  hacking course to perform illegal activities outside of the  classroom.
Keywords: Ethical Hacking; Hacking; Hacking Education; Hacking Ethics; White Hat Hacking